Hypoxia-Induced Adipose Lipolysis Requires Fibroblast Growth Factor 21 - Wu, Guicheng; Liu, Yanlong; Feng, Wenke; An, Xuan; Lin, Wenhui; Tang, Chengwei (Frontiers in Pharmacology, 2020)
Fibroblast growth factor 21 (FGF21) is a recently discovered hepatokine that regulates lipid and glucose metabolism and is upregulated in response to numerous physiological and pathological stimuli. Herein, we demonstrate that both physical and chemical hypoxia increase the systemic and hepatic expression of FGF21 in mice; by contrast, hypoxia induces a reduction of FGF21 expression in hepatocytes, indicating that hypoxia-induced FGF21 expression is differentially regulated in intact animals and in hepatocytes. Furthermore, we demonstrate that hypoxia treatment increases hormone-sensitive lipase-mediated adipose tissue lipolysis in mice, which is reduced in Fgf21 knockout mice, thereby implying that FGF21 plays a critical role in hypoxia-related adipose lipolysis. Adipose tissue lipolysis causes an increase in the amount of circulating free fatty acids, which leads to the activation of peroxisome proliferators-activated receptor alpha and an increased expression of FGF21 in hepatocytes. We further show that hypoxia-induced elevation of reactive oxygen species, but not the hypoxia-inducible factor, is responsible for the lipolysis and FGF21 expression. In conclusion, our data clearly demonstrate that FGF21 plays a critical role in hypoxia-induced adipose lipolysis, which induces hepatic expression of FGF21. Clarification of hypoxia-regulated FGF21 regulation will enhance our understanding of the pathophysiology of hypoxia-related diseases, such as sleep disorders and metabolic diseases.